Studies in the History of the English Feudal Barony - Painter, Sidney, 1902-1960 (Book collections on Project MUSE., 2020)
Sidney Painter explores the Angevin and Plantagenet baronage by surveying the methods that barons used to increase their prestige. His book challenges the traditional view of the Hundred Years' War as pivotal to the transition from twelfth-century lords and vassals to the nobility of the fifteenth century; from Painter's perspective, the feudal structure of the military had dissipated by the thirteenth century.